O discurso sobre políticas educacionais presente na revista educação & sociedade (1978 – 1988) - Silva, Ana Lucia Calbaiser da (Universidade Federal de São Carlos, 2016)
The aim of this study is to investigate the discourse of the academic community on educational public policies, that have been made in Brazil, in a period marked by the transition from military regime to democracy. As object of analysis, we chose the Educação & Sociedade magazine (1978-1988), whose maintainer is the Centro de Estudos Educação & Sociedade (CEDES). Edited since 1978, this magazine followed the development of important historical moments that marked Brazilian society, such as distension process of the military regime and the country's democratization. The magazine actively participated in these historic moments, making it a suitable space for debate and discussion on the directions of educational public policies. Currently, the magazine is considered a significant national journal in the field of education. The methodology used in this research was Epistemology Policy, which allowed us to explain and categorize both the intellectuals who broadcasted his studies in this journal as the discourses present in the work of these intellectuals. In the period investigated, Educação & Sociedade magazine proved to be a scientific communication vehicle of academic intellectuals. These are formed, mostly by intellectuals who had maximum doctorates and worked in the field of Education. Publishing, mostly single authorship studies, these intellectuals were active, mainly in public institutions of higher education. Although most of the authors had no direct link to the magazine, found that the intellectuals who published several studies that form worked in the process of organizing Educação & Sociedade magazine. The speeches published in the journal had a prescriptive and imperatives facing the criticism of the military regime and the pursuit of transforming reality. They were based on a political perspective guided by a reformist vision of public policies and a philosophical perspective based on the concept of praxis. In this conception, critical reflection is considered essential for the transformation of reality. With this political and philosophical perspective, they were published in the journal reflective and critical studies on Brazilian education. These studies emphasized the authoritarian and oppressive character of public policies of the military regime and denounced their ills for education. Moreover, there was criticism of the educational policies of welfare character, populist and clientelist, compensatory programs, policies that preserved and deepened social inequalities and education funding policies. On the other hand, the magazine published studies in support of the democratization of education policies, policies that had the goal of ensuring quality education for all and defense policies of secular education. The magazine was also a space for the discussion of transformative and democratic practices. Thus, the magazine defended the popular education and also participated in the constituent, forwarding along with other representative bodies, a proposal for constitutional principles for education. These principles, which also guided the editorial line of the magazine over the analysis period were the defense of public education for all, free, secular and democratic.
Keywords: Políticas públicas educacionais; Educação & sociedade; Comunidade acadêmica; Educational public policies; Educação & Sociedade; Academic community; CIENCIAS HUMANAS::EDUCACAO